2002
DOI: 10.1046/j.1365-2869.2002.00277.x
|View full text |Cite
|
Sign up to set email alerts
|

Time‐courses in renin and blood pressure during sleep in humans

Abstract: SUMMARY We previously described a strong concordance between nocturnal oscillations in plasma renin activity (PRA) and the rapid eye movement (REM) and non-REM (NREM) sleep cycles, but the mechanisms inducing PRA oscillations remain to be identi®ed. This study was designed to examine whether they are linked to sleep stage-related changes in arterial blood pressure (ABP). Analysis of sleep electroencephalographic (EEG) activity in the delta frequency band, intra-arterial pressure, and PRA measured every 10 min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 32 publications
2
13
1
Order By: Relevance
“…The modulation of RAAS found in this study might be secondary to changes in blood pressure although previous reports have found a close relationship between renin secretion and sleep stages with increased renin levels during REM stages (4). The same group later reported that changes in sympathetic tone during sleep leading to MAP reduction preceded the increase in renin, pointing toward pressure-related changes rather than a central effect of sleep (5). We find that nonsleep increases blood pressure and decreases RAAS hormone levels.…”
Section: Discussioncontrasting
confidence: 49%
“…The modulation of RAAS found in this study might be secondary to changes in blood pressure although previous reports have found a close relationship between renin secretion and sleep stages with increased renin levels during REM stages (4). The same group later reported that changes in sympathetic tone during sleep leading to MAP reduction preceded the increase in renin, pointing toward pressure-related changes rather than a central effect of sleep (5). We find that nonsleep increases blood pressure and decreases RAAS hormone levels.…”
Section: Discussioncontrasting
confidence: 49%
“…Although 70° HUT and −55 mmHg LBNP show similar cardiovascular responses and lead to similar amounts (approximately 600 mL) of venous pooling in the legs [15], endocrine effects of these stressors may be different because splanchnic pooling increases with passive head‐up tilt and drops during LBNP. This might explain a slight drop in mean arterial pressure with LBNP, possibly compensated for by a greater increase in PRA [20] compared with HUT, where arterial pressure increases, thereby lessening the magnitude of the reflex PRA response. It has been observed previously that graded doses of ACTH infusion lead to a linear increase in plasma aldosterone without changes in plasma sodium, potassium or PRA [21].…”
Section: Discussionmentioning
confidence: 99%
“…2831 As described above, normal sleep is accompanied by the so-called “dipping” of systolic and diastolic BP. A study by Charloux et al 29 that continuously recordedthe arterial BP of healthy volunteers using PSG identified this decrease in BP as the event that initiates a robust nocturnal elevation of plasma renin activity (PRA). Once sleep is initiated, sympatho-vagal balance is exquisitely modulated by the NREM-REM cycle, which is best quantified by assessing oscillations of EEG slow-wave activity using spectral analysis (Figure 2).…”
Section: Direct Impact Of Sleep Disorders On Ckdmentioning
confidence: 99%